LITERATURE REVIEW: ANALISIS PENYEBAB KEJADIAN STUNTING PADA BALITA DI PROVINSI JAWA TIMUR: Literature Review: Analisis Penyebab Kejadian Stunting pada Balita di Provinsi Jawa Timur - Pertiwi, Aisyah Noer Auliyah Madani; Hendrati, Lucia Yovita (Amerta Nutrition, 2023)
Background: The prevalence of stunting in East Java Province in 2022 reached 19.2%, showing a decrease compared to 2021, which recorded a prevalence rate of 23.5%. Despite the declining trend in stunting prevalence in East Java, the province has not yet achieved the Renstra target, which stipulates that the prevalence of stunting should decrease to 18.4% by 2022. Objectives: This study aims to investigate further the causes of stunting incidents in East Java Province. Methods: The method employed in this research is a literature review, where data sources are obtained using the Google Scholar electronic database. The research search process follows the PICOS protocol, formulating keywords using Boolean Operator techniques. The keywords used are "factors" AND "causes" OR "relationships" OR "risks" AND "stunting" AND "infants" OR "toddlers" OR "children." The selection of studies to be included in the review is adjusted to inclusion criteria: studies published in the last ten years (2013-2023), written in Indonesian and English, full-text, published, and open access. Exclusion criteria include age range, non-observational research, and studies that do not discuss the causes of stunting. Results: A total of 13 studies were used in compiling this review. The location characteristics of the studies were found in 10 Districts/Cities in the East Java Province. Over the past ten years, various factors have been recognized as causes of stunting based on the identified research publications. These factors include parenting styles, Clean and Healthy Living Behavior (PHBS), economic status, educational history of birth, history of infectious diseases, and maternal pregnancy history. Conclusions: The primary research focus on stunting incidents in toddlers in East Java Province is the parenting style provided by mothers. The level of maternal knowledge regarding Exclusive Breastfeeding (ASI), provision of Complementary Feeding (MPASI), and the intake of foods consumed by toddlers has a significant correlation with the occurrence of stunting and the developmental progress of children.